The impact of advanced technological developments on solar PV value chain. (2021) - Udayakumar, M.D.; Anushree, G.; Sathyaraj, J.; Manjunathan, A.
Abstract: The electricity sector has largely started to employ solar photovoltaic (PV) systems as an alternative and clean source of energy. Here the goal is to offer ever more effective PV conversion solutions. These solutions lead towards the innovations throughout the solar PV value chain. The cell efficiency plays a vital role in manufacturing of PV modules and materials as it directly influences in the reduction of cell processing costs. This study addresses and examines the progress in innovations in themanufacturing of solar PV modules and materials, emerging application areas apart from the fields and rooftops, O&M services and finally the end-of-life material recycling of solar PV cells.